Analyze Marketing Strategies Through Instagram to Increase Sales Volume in The Bouquet Business eightbucket.id - Amaria, Hanik (Universitas Islam Balitar, 2023)
Nowadays the culture gives bouquets to special people as a form of respect, giving congratulations or gifts as a sign of affection. A bouquet can be a flower arrangement, snack or item that is liked by the recipient that is assembled very beautifully so as to make the recipient flattered and happy. The purpose of this study is to find out how the marketing strategy through Instagram to increase the sales volume of bouquets flowers on eightbucket.id. The results showed that the 4P marketing strategy, namely Product, Price, Promotion and Place carried out by the owner through his Instagram account, is very complete and attractive. Information about products by uploading various variations of bouquets with interesting captions, always updating reels and IG stories and providing give away makes potential consumers feel interested in becoming followers and buying products made so that it shows a very significant increase in sales volume.